What Macroeconomists Should Know about Health Care Policy - Heller, Peter; Hsiao, William (Washington, D.C. : International Monetary Fund, 2007)
This primer explains why macroeconomists need to be concerned with issues of health policy and elaborates the essential information that a macroeconomist should know in providing inputs to discussions on health sector policy. The primer illustrates how these issues and the range of appropriate policy options may differ depending on the state of development of an economy and the particular approach taken by a country in structuring its health system. The primer also highlights the appropriate roles for the state and market in health care financing and provision, taking account of the various sources of market failure in the health sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet